Effect of Mineral Phase Ratios on Reduction Behavior of Multi-component Calcium Ferrite Extracted from Iron Ore Sinter - Maruoka, Daisuke; Kimura, Nanase; Kasai, Eiki; Murakami, Taichi (Tetsu to hagane, 2025)
In this study, the method to extract multi-component calcium ferrite (CF) into actual iron ore sinter is proposed and its reducibility is investigated under N2–CO–CO2 atmosphere. Actual iron ore sinter are pre-reduced at 500°C for 3 h in N2–CO–CO2–H2–H2O atmosphere and then sample particles containing mainly multi-component CF are successfully obtained through crashing and wet magnetic separation.In the isothermal reduction at 700–800°C, the reduction rate shows positive correlation with compositions of SFCA-I and SFCA-III up to early stage of reduction, and the negative correlation is obtained with SFCA. However the relationship is reversed, for example at 750°C for approximately 90 s. After approximately 380 s, there is no longer any correlation between SFCA and the reduction rate. It indicates that SFCA-I and SFCA-III are already reduced to intermediate products up to 90 s and the reduction of SFCA affects the reduction rate up to 360 s at 750°C.In the heating reduction using in-situ XRD, the formation of wustite is identified along with the decrease in the intensity of multi-component CF from around 600°C. The intensity of SFCA-III decreases from around 550°C and disappears at 760°C, whereas the SFCA-I decreases more gradually. It is known as the multi-component CF consists of series of spinel and pyroxene structure. Since the proportion of S units is SFCA-III > SFCA-I > SFCA, it implies that the reduction of Fe ions advances in S units than in P units.